Nonlinear passive tremor control of human arm. (1st January 2021) - Ture Savadkoohi, A.; Lamarque, C.-H.; Goossaert, C.
Highlights: Nonlinear locomotion equations of human arm are investigated. Linear frequencies vary with respect to the postures. The system is coupled to a nonlinear energy sink. Fast and slow dynamics are revealed. Abstract: An academic model for passive vibration control of human arm suffering from essential tremors is proposed. The nonlinear uncontrolled system equations are linearised around arbitrary postural positions showing variations of linear natural frequencies as functions of postural positions. The coupled system, i.e. the model of the arm with the attached nonlinear absorber, is treated via a time multiple scale method leading to detection of fast and slow systems dynamics. These dynamics provide design tools for tuning parameters of the nonlinear absorber.